Strategia zarządzania kluczowymi pracownikami w procesach międzynarodowych fuzji i przejęć - Buchelt-Nawara, Beata (The strategy of the key employees management during international M&As, 2006)
Access to valuable intangible assets, especially human capital, becomes one of the most important reasons for the companies to merge with or acquire other companies. However, one has to realize that human capital role in the M&As processes is not only limited to its influence on the intangible assets value. It also becomes the key success factor of the M&As processes and the potential source of the future competitive advantage. Due to the fact that the importance of human capital during international M&As increases, it is significant to define activities that help the merging organizations manage key employees, who are the most valuable assets for the organizations. In the article the author describes the activities which should be taken by the merging organizations in order to identify and keep the key employees during the process of an international merger or acquisition.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 174-183